The Role of Crustal Buoyancy in the Generation and Emplacement of Magmatism During Continental Collision. (5th November 2019) - Schliffke, Nicholas; van Hunen, Jeroen; Magni, Valentina; Allen, Mark B.
Abstract: During continental collision, considerable amounts of buoyant continental crust subduct to depth and subsequently exhume. Whether various exhumation paths contribute to contrasting styles of magmatism across modern collision zones is unclear. Here we present 2D thermomechanical models of continental collision combined with petrological databases to investigate the effect of the main contrasting buoyancy forces, in the form of continental crustal buoyancy versus oceanic slab age (i.e., its thickness). We specifically focus on the consequences for crustal exhumation mechanisms and magmatism. Results indicate that it is mainly crustal density that determines the degree of steepening of the subducting continent and separates the models' parameter space into two regimes. In the first regime, high buoyancy values ( ∆ρ > 500 kg/m 3 ) steepen the slab most rapidly (to 45–58°), leading to opening of a gap in the subduction channel through which the subducted crust exhumes ("subduction channel crustal exhumation"). A shift to a second regime ("underplating") occurs when the density contrast is reduced by 50 kg/m 3 . In this scenario, the slab steepens less (to 37–50°), forcing subducted crust to be placed below the overriding plate. Importantly, the magmatism changes in the two cases: Crustal exhumation through the subduction channel is mainly accompanied by a narrow band of mantle melts, while underplating leads to widespread melting of mixed sources. Finally, we suggest that the amount (or density) of subducted continental crust, and the resulting buoyancy forces, could contribute to contrasting collision styles and magmatism in the Alps and Himalayas/Tibet. Plain Language Summary: Continental collision follows the end of oceanic subduction and leads to high elevation ranges such as the Alps, the Tibetan Plateau/Himalayas, and the Zagros mountains. It is not clear why their structures and distributions of magmatism are so different: The Alpine range is narrow with only a few magmatic bodies within it. In the Tibetan‐Himalayan system, the plateau is wide (>1, 000 km across) and has numerous magmatic centers that postdate initial collision. Furthermore, Indian crust (i.e., the upper part of the Indian continent) has been detected beneath Tibet, which is not the case in the Alps. In this study, we use computational models to investigate how buoyancy from subducting continental crust affects generation of magmatism during continental collision. We find that the total buoyancy determines whether all continental material stays close to the contact between the colliding continents or if some of the continental material is placed below the overriding continent. In the first case, only small areas melt. In the second case, we see widespread melting of material. These model results fit observations and suggest that proportionally (i.e., per unit trench) less crust has subducted in Tibet/Himalayas than in the Alps to make these areas so strikingly different. Key Points: We analyse buoyancy forces in 2D thermomechanical‐petrological models of continental collision and resulting postcollisional magmatism Crustal buoyancy controls whether subducting crust exhumes between plates with only mantle melts or underplates with mixed melting Timing and distribution of crust and melting for two endmembers fits Alps and Himalaya/Tibet